Study of Climate Change Impact to Local Rainfall Distribution in Lampung Provinces - Tumiar Katarina Manik; Bustomi Rosadi; Eva Nurhayati (Forum Geografi, 2014)
Global warming which leads to climate change has potential affect to Indonesia agriculture activities and production. Analyzing rainfall pattern and distribution is important to investigate the impact of global climate change to local climate. This study using rainfall data from 1976-2010 from both lowland and upland area of Lampung Province. The results show that rainfall tends to decrease since the 1990s which related to the years with El Nino event. Monsoonal pattern- having rain and dry season- still excist in Lampung; however, since most rain fell below the average, it could not meet crops water need. Farmers conclude that dry seasons were longer and seasonal pattern has been changed. Global climate change might affect Lampung rainfall distribution through changes on sea surface temperature which could intensify the El Nino effect. Therefore, watching the El Nino phenomena and how global warming affects it, is important in predicting local climate especially the rainfall distribution in order to prevent significant loss in agriculture productivities.